Akses pelayanan kesehatan terhadap kejadian tuberkulosis resisten obat - Ahmad Dimas Rasyidin; Ema Novita Deniati; Siti Nurrochmah; Supriyadi Supriyadi (Holistik Jurnal Kesehatan, 2026)
Background: Drug-resistant tuberculosis (Drug-resistant TB) is a serious public health challenge in Indonesia. Limited access to healthcare services, delayed diagnosis, and barriers to treatment contribute to the development of drug resistance. Purpose: This study aims to analyze the relationship between access to healthcare services and the incidence of DRT. Method: This quantitative observational study with a cross-sectional design involved 1,298 respondents selected through purposive sampling. Data were obtained from the 2023 Indonesian Health Survey. The incidence of DRT was designated as the dependent variable, while access to healthcare services was the main independent variable, with confounding factors including residence, gender, age, education, employment status, and economic status. Data analysis was performed using univariate tests, chi-square tests, and logistic regression. Results: A total of 39.06% of respondents were diagnosed with DRT, and 88.98% experienced difficulty accessing healthcare services. Multivariate analysis showed no significant association between access to healthcare services and DRT. Age ≥65 years was the only factor significantly associated with drug-resistant TB (DR-TB), and other variables did not show a significant effect. Conclusion: Access to health services as measured in this study did not significantly influence DR-TB due to its limited scope, which only captured the physical dimension of access. Suggestion: Future research should use multidimensional access indicators to understand the factors influencing DR-TB in Indonesia.   Keywords: Access; Drug Resistance; Health Services; Tuberculosis (TB).